Aesthetic Qualities and Aesthetic Judgments - Katalynas, Antanas (Sociologija. Mintis ir veiksmas, 2001)
This is an introductory article to the translation of Frank Sibley’s “Aesthetic Concepts”. The problem of the aesthetic as it has formed in the controversies of theoretical trends is analysed here. The article provides with thorough consideration of Frank Sibley’s conception, developed in his works. The indirect controversy of author’s position towards the objectivist understanding of aesthetic qualities and aesthetic judgments, the original character of his theoretical system is demonstrated.